Experimental Study on Nano-SiO2 Improving Concrete Durability of Bridge Deck Pavement in Cold Regions - Youkun Cheng; Zhenwu Shi (Advances in Civil Engineering)
In order to reduce early damage of bridge deck pavement concrete in cold regions, a certain content of nano-SiO2 is added into the concrete to enhance its durability. Through tests on four durability indexes, strength, frost resistance, resistance to Cl− ion permeability, and abrasion resistance of concrete with 1% nano-SiO2 content and concrete without nano-SiO2, the ability of nano-SiO2 to improve the concrete durability of bridge deck pavement is evaluated. The results of tests and analysis show that the incorporation of nano-SiO2 greatly improves the four durability indexes. Nano-SiO2 effectively absorbs the calcium hydroxide released early by the hydration of cement, increases the calcium silicate hydrate content, and elevates the interface between the paste and aggregate of the hardened cement, which improves the durability of the concrete.